Mesoporous MgO promoted with NaNO3/NaNO2 for rapid and high-capacity CO2 capture at moderate temperatures - Zhao, Xiao; Ji, Guozhao; Liu, Wen; He, Xu; Anthony, Edward J.; Zhao, Ming (Elsevier, 2017)
A series of mesoporous MgO samples with different morphologies were synthesized through a simple hydrothermal treatment and NaNO3/NaNO2 were used as promoters to enhance CO2 capture capacity at an intermediate temperature range (200–400 °C). The effects of hydrothermal solution pH and content of promoters were examined to determine the optimal synthesis conditions. The influence of operational temperatures, CO2 partial pressure, and performance over repeated cycles was investigated and the reaction mechanism was discussed. The mesoporous MgO promoted by NaNO3/NaNO2 exhibited a CO2 capture capacity as high as 19.8 mmol g−1 at 350 °C in the presence of 0.85 bar of CO2 within only 50 min. A “three-stage” reaction process was proposed based on a detailed sorption kinetics study, namely Stage I: initiating interactions between CO2 and exposed MgO; Stage II: generation and accumulation of Mg2+ and CO32−; and Stage III: fast carbonation. Gradual deterioration of sorbents was found over the first 5 cycles followed by stable regenerability in the 5−15th cycles. A kinetic study of the 15th cycle suggests that the deactivation of sorbents inhibited the accumulation of Mg2+ and CO32− in Stage II and suppressed the carbonation in Stage III. A range of characterizations were undertaken revealing the morphology and structure of both fresh and regenerated sorbents. The results confirmed that, other than the sintering effect due to phase transition, the transformation of MgO skeleton is also an important contributor to the gradual deactivation of the sorbents over the first 5 cycles. More severe sintering effect under harsh decarbonation conditions suppressed the stability of the sorbents over cycles.
Keywords: CO2 capture; Moderate-temperature sorbent; Rapid absorption; Mesoporous MgO; Molten state promoters